Repeated percutaneous cryoablation and radiofrequency ablation for renal tumors in a solitary kidney: report of two cases - Ulys, Albertas; Čerškutė, Minija; Naruševičiūtė, Ieva; Trakymas, Mantas; Kulboka, Arūnas (Lietuvos chirurgija, 2016)
Introduction Percutaneous cryoablation and radiofrequency ablation are options of minimally invasive treatment while maximizing nephron preservation. It is increasingly used in patients with comorbid conditions, multiple renal cell carcinomas, for patients with a single kidney and/or inherited renal cancer syndromes especially in situations when there is a need to preserve renal function. The aim of this presentation is to show the benefits (effectiveness and safety) of cryoablation for the patients with a solitary kidney from our experience. Case reports We present 2 cases of the patients with a solitary kidney and solid renal masses of <4 cm who underwent percutaneous cryoablation and radiofrequency ablation multiple times. A follow up computed tomography was performed at 1 day, 3, 6 and 12 months and every 6 months thereafter, along with physical examination, urine analysis and serum creatinine. Both patients tolerated renal cryoablation and radiofrequency therapy well with no postoperative complications and no change in renal function, there was no significant change in serum creatinine from preoperative values. Both patients had complete tumor ablation after the treatment. Conclusion Although it is not possible to draw definite conclusions about the safety and efficacy of these techniques from two successful cases, however, these cases demonstrate that these minimally invasive treatment techniques allow kidney cancer to be treated with much less disruption of patients’ lives and helps to achieve acceptable oncological results.